Position-specific differences in speed profiles among National Football League Scouting Combine participants - Gillen, Z. M. (The Journal of Strength and Conditioning Research, 2025)
This study examined the relationships between speed profiles and athletic performance measurements from the National Football League (NFL) Scouting Combine, and position-specific differences in speed profiles. Subjects included NFL Scouting Combines participants with valid scores for the 40-yard dash, as well as the 10- and 20-yard splits of the 40-yard dash (n = 2,156). Subjects were divided into the following position groups: defensive backs (DBs, n = 421), defensive linemen (DL, n = 356), linebackers (LBs, n = 261), offensive linemen (OL, n = 354), running backs (RBs, n = 217), tight ends (TEs, n = 122), quarterbacks (QBs, n = 108), and wide receivers (WRs, n = 317). Performance measures included 40-yard dash time (with 10- and 20-yard split times), bench press repetitions to failure, vertical jump height, broad jump distance, pro-agility time, and L-cone drill time. The 40-yard dash and its splits calculated vmax, t, and amax to reflect speed profiles. One-way analysis of variances examined position-related differences. Pearson`s product moment correlation coefficients examined relationships between performance measures and speed profile variables. Skill positions (DB and WR) had the greatest vmax and amax, and lowest t, followed by big skill positions (LB, RB, TE, QB), followed by DL, then OL with the lowest vmax and amax, and highest t. For skill and big skill positions, vmax, t, and amax exhibited greater relationships with combine measures, whereas OL generally had the lowest relationships. The position-specific differences in this study demonstrate potential areas of strength and weakness for certain positions. This may help guide strength and conditioning coaches desiring to improve position-specific speed and acceleration capabilities for American football players.